Evaluating performance of carbon fiber-reinforced pavement with embedded sensors using destructive and non-destructive testing - Maryam Monazami; Ashutosh Sharma; Rishi Gupta (Case Studies in Construction Materials, 2022)
Installation of concrete pavement at the curb travel lane at the bus stop is a common way to improve the resistance of bus pads to environmental and petroleum deterioration in Canada. The Satisfactory condition of concrete pavements remains a key consideration in the development of infrastructure, especially in countries with an aggressive environment. Innovative materials that could remarkably increase the service life of infrastructure are being researched and developed over decades. This paper aggregates the real-time comparison between the performance of a carbon fiber-reinforced concrete (CFRC) bus pad and a normal concrete bus pad. A series of wireless sensors such as temperature and humidity sensors, thermocouples and strain gauges were embedded in both pavements during the construction. Additionally, a series of six piezoelectric patches were embedded in the concrete in each bus pad. Visual monitoring exhibited that the carbon fiber-reinforced bus-pad remained cracked free while exhibiting some balling of carbon fibers on the surface of pavement whereas the normal concrete bus pads exhibited several hairline cracks in the first 10 days of construction. Along with the visual monitoring using a thermal imaging camera (FLIR), data was acquired regularly from both bus-pads at regular intervals. After 28 days of construction, Non-destructive tests (NDT) including Schmidt Hammer (SH), Electrical Resistivity (ER) and Ultrasonic Pulse Velocity (UPV) were conducted on both the bus pads. When compared to normal concrete bus pads, which have electrical resistivities of roughly 30 kΩ-cm, CFRC bus pads showed extremely low electrical resistivity. Schmidt hammer and UPV both revealed degradation in the normal concrete bus pad in comparison to the CFRC bus pad. Several clusters of very low UPV values were observed in the location of bus pad cracks. The lesser values in the CFRC bus pad are indicative of the scatter in the wave energy due to the presence of carbon fibers.